Effects of Ceramic Translucency and Thickness on Polymerization of a Photosensitive Resin Cement - Abdullah Barazanchi; Jaafar Abduo; Yvonne Min-Joo Lee; Min-Suk Lee; Kai Chun Li (MDPI AG, 2023)
We investigated the effects of lithium disilicate ceramic thickness and translucency on the degree of polymerization of light-cured resin cement using the measure of hardness. Lithium disilicate specimens of three translucencies (low, medium and high) were prepared to four thicknesses (0.5, 1.0, 2.0 and 3.0 mm). A light-cured resin cement was cured through each of the ceramic specimens using a handheld curing light for 50 s. A 3D printed jig was used to achieve a uniform thickness of the resin cement. Directly cured resin cement was used as the control. Hardness was measured using nano-indentation to determine the degree of polymerization of the resin cement. Two-way ANOVA and Tukey post hoc tests were used to evaluate interaction between translucency and thickness. Hardness values from control specimens were assessed using the two-tailed t-test with the Bonferroni approach. The translucency of the specimens significantly influenced the hardness (p < 0.001), where a negative linear relationship between cement hardness and ceramic thickness was present for low translucency and high translucency. However, at a 0.5 mm thickness, all specimens showed similar hardness regardless of the translucency. The translucency of ceramics affected the hardness, and hence polymerization, of light-cure resin cement. However, the effect of increased thickness was a more significant factor.